2022
DOI: 10.7150/thno.72291
|View full text |Cite
|
Sign up to set email alerts
|

DUSP2-mediated inhibition of tubular epithelial cell pyroptosis confers nephroprotection in acute kidney injury

Abstract: Rationale: Acute kidney injury (AKI) is pathologically characterized by renal tubular epithelial cell (RTEC) death and interstitial inflammation, while their pathogenesis remains incompletely understood. Dual-specificity phosphatase 2 (DUSP2) recently emerges as a crucial regulator of cell death and inflammation in a wide range of diseases, but its roles in renal pathophysiology are largely unknown. Methods: The expression of DUSP2 in the kidney was characterized by histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The AKI-to-CKD mouse model refers to previous studies ( Xiong et al, 2022 ). Briefly, 8–12 weeks male mice were anesthetized, followed by an abdominal incision, and the renal pedicles of both kidneys were clamped for 32 min to induce IRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AKI-to-CKD mouse model refers to previous studies ( Xiong et al, 2022 ). Briefly, 8–12 weeks male mice were anesthetized, followed by an abdominal incision, and the renal pedicles of both kidneys were clamped for 32 min to induce IRI.…”
Section: Methodsmentioning
confidence: 99%
“…Scr and BUN were detected using a commercial kit (NJJCBIO, China) according to previously reportt following manufacturer’s instructions ( Xiong et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to this, one pathological feature of AKI is inflammation in the renal interstitium. 17 This inflammatory response represents the primary host defense mechanism against infection and plays a crucial role in initiating and supporting the necessary repair processes for functional recovery following injury. 18 Classic inflammatory indicators, including the white blood cell count and its subtypes, notably the neutrophil and lymphocyte counts, have a well-established place in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that vitamin D3 can reduce the production of ROS and inhibit the nuclear factor kappa B (NF-κB) signaling pathway, thus hindering pyroptosis [31]. Salvianolic acid B, a water-soluble compound extracted from Salvia, has potent antioxidant properties, and Pang et al [32] discovered that it significantly decreases the expression of NLRP3, Caspase-1, GSDMD, and IL-1β in kidney tissues of the IRI-AKI group. In vitro experiments have further confirmed that salvianolic acid B pretreatment helps increase Nrf2 levels by inhibiting oxidative stress, pro-inflammatory cytokines, and NLRP3 inflammasome activation, reducing pyroptosis.…”
Section: Ischemia-reperfusion Injury Akimentioning
confidence: 99%